Oligo-carrageenan kappa increases NADPH, ascorbate and glutathione syntheses and TRR/TRX activities enhancing photosynthesis, basal metabolism, and growth in Eucalyptus trees - González, Alberto; Moenne, Fabiola; Gómez, Melissa; Sáez, Claudio A.; Contreras, Rodrigo A.; Moenne, Alejandra (Frontiers in Plant Science, 2014)
In order to analyze the effect of OC kappa in redox status, photosynthesis, basal metabolism and growth in Eucalyptus globulus, trees were treated with water (control), with OC kappa at 1 mg mL-1, or treated with inhibitors of NAD(P)H, ascorbate (ASC) and glutathione (GSH) syntheses and thioredoxin reductase (TRR) activity, CHS-828, lycorine, buthionine sulfoximine (BSO) and auranofin, respectively, and with OC kappa, and cultivated for 4 months. Treatment with OC kappa induced an increase in NADPH, ASC, and GSH syntheses, TRR and thioredoxin (TRX) activities, photosynthesis, growth and activities of basal metabolism enzymes such as rubisco, glutamine synthetase (GlnS), adenosine 5´-phosphosulfate reductase (APR), involved in C, N and S assimilation, respectively, Krebs cycle and purine/pyrimidine synthesis enzymes. Treatment with inhibitors and OC kappa showed that increases in ASC, GSH and TRR/TRX enhanced NADPH synthesis, increases in NADPH and TRR/TRX enhanced ASC and GSH syntheses, and only the increase in NADPH enhanced TRR/TRX activities. In addition, the increase in NADPH, ASC, GSH and TRR/TRX enhanced photosynthesis and growth. Moreover, the increase in NADPH, ASC and TRR/TRX enhanced activities of rubisco, Krebs cycle and purine/pyrimidine synthesis enzymes, the increase in GSH, NADPH, and TRR/TRX enhanced APR activity, and the increase in NADPH and TRR/TRX enhanced GlnS activity. Thus, OC kappa increases NADPH, ASC and GSH syntheses leading to a more reducing redox status, the increase in NADPH, ASC, GSH syntheses and TRR/TRX activities are cross-talking events leading to activation of photosynthesis, basal metabolism and growth in Eucalyptus trees.